Developing the Philippine blue economy: Opportunities and challenges in the ocean tourism sector - Maria Angela G. Zafra (Asian Development Bank Institute (ADBI), 2021)
Ocean tourism contributes significantly to the economy of the Philippines, an archipelagic nation with one of the longest coastlines in the world and one of the best marine environments in terms of biodiversity. This paper aims to explore how ocean tourism and economic development intertwine in archipelagic nations, examining national statistical data on tourism and economic development in the Philippines over the last several years. Furthermore, it discusses the policy landscape and identifies the enabling and disabling factors for the development of ocean tourism in the Philippines. It indicates how inclusive models can be a catalyst for sustainable tourism through a case analysis of El Nido Resorts, a tourism enterprise operating luxury resorts within the protected area of El Nido, Palawan. It also discusses recommendations of practical policy relevance based on the opportunities and challenges of sustainable ocean tourism in the Philippines.
Keywords: L8; O1; M2; Q5; Z3; 330; ocean; tourism; blue economy; development